Religious Symbolism and Political Resistance: Navalny’s Martyr Narrative in the Russian Opposition - Nadezhda Beliakova; Zhanna Timofeeva (Religions)
The death of Russian dissident Alexey Navalny in a far-northern colony after three years of imprisonment was declared a martyrdom by the Russian opposition, reflecting the sentiments of a part of Russian society. This unexpected reference to martyr narrative by a largely secular and anti-clerical opposition has set a significant precedent when religious discourse is instrumentalized not only by official propaganda but also by its critics. The authors posit that the construction of a martyr narrative is deeply political, being a part of contemporary ideological war. This article argues that Alexey Navalny’s death and its subsequent sacralization by opposition figures represent a significant moment in contemporary Russian politics. By adopting religious narratives and symbols, the opposition not only mobilizes support but also challenges the regime’s monopoly on ideological and religious discourse. However, this strategic use of martyrdom carries inherent contradictions, reflecting the opposition’s ambivalent relationship with religion and the Russian Orthodox Church.